Effects of Approximation and Close-Fitting Technique of Corona Model on Neon Soft X-Ray Emission in 3-kJ Plasma Focus - Abd Rashid, Natashah; Mohamad, Saiful Najmee; Chaudhary, Kashif Tufail; Lee, Sing; Saw, Sor Heoh; Ali, Jalil (IEEE, 2015)
In plasma focus (PF), the thermodynamic parameters such as ion fraction α, effective ionic charge number Zeff , and effective specific heat ratio γ at different temperatures may be calculated by corona model (CM). In the Lee model code, the neon Zeff and γ are stored in subroutines using convenient tables and polynomials derived from the CM (we call this approach approximated CM). In this paper, the thermodynamic parameters of the CM are close fitted to the data, thus replacing the approximate CM data with a more accurate close-fitting CM (CFCM). The comparisons of the Lee model code using the approximated CM and CFCM subroutines are conducted, with the main emphasis on optimum neon soft X-ray (SXR) emission and their properties. The suitable focus pinch temperature window of 200–500 eV is applied to generate the optimum neon SXR yield (Ysxr). The optimum neon Ysxr is found to be 3.19 and 3.49 J at the optimum pressure P0 = 3.1 torr with approximated CM and CFCM subroutines, respectively. A high optimum value of SXR yield is obtained using CFCM subroutines in the Lee model, which is nearer to the experimental value compared with the approximated CM subroutines. The use of CFCM in the Lee model contributes to better estimation for further numerical experiment studies and gives confidence that the model is sufficiently realistic in describing the PF dynamics and SXR emission.